1989
DOI: 10.1677/joe.0.1200161
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of the human Leydig cell to radiation damage is dependent upon age

Abstract: Testicular function was studied in three groups of patients previously treated for malignant disease, and a control group of adult males. The adult patients in groups one and two underwent unilateral orchidectomy for a testicular tumour but only in group two was this followed by post-operative high-dose irradiation (30 Gy) to the remaining testis. Four of the five boys in group three had a unilateral orchidectomy between the ages of 1 and 4 years and all five received a similar dose of irradiation (27.5-30 Gy)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1
7

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(105 citation statements)
references
References 0 publications
4
93
1
7
Order By: Relevance
“…The boys showed no relationship between age at BMT and plasma gonadotropin concentrations. This is in disagreement with the data reported after testicular irradiation for leukemia, 17,18 or conditioning for BMT, 12 showing that younger boys are likely to have Leydig cells that are more vulnerable to irradiation. The reverse was reported by Mertens et al, 13 who found that the proportion of individuals with increased LH at their last clinical evaluation increased significantly with age at BMT.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The boys showed no relationship between age at BMT and plasma gonadotropin concentrations. This is in disagreement with the data reported after testicular irradiation for leukemia, 17,18 or conditioning for BMT, 12 showing that younger boys are likely to have Leydig cells that are more vulnerable to irradiation. The reverse was reported by Mertens et al, 13 who found that the proportion of individuals with increased LH at their last clinical evaluation increased significantly with age at BMT.…”
Section: Discussioncontrasting
confidence: 69%
“…None of them had any central nervous system involvement at diagnosis, nor had they been given irradiation other than total body irradiation (TBI). Chronic graft-versus-host disease occurred in 28 cases (cases 9,11,12,17,18,21,[23][24][25]27, 29 and 31 in girls and cases 5,9,11,12,15,18,19,21,26,29,30, 33, 35-37 and 39 in boys) and had been treated with corticosteroids and cyclosporine. All were in remission without complications.…”
Section: Patientsmentioning
confidence: 99%
“…10 The number of primordial follicles present at the time of treatment, together with the dose received by the ovaries, will determine the fertility ''window'' and influence the age of premature ovarian failure. Ovarian failure has been reported in 90% of patients followed long term after TBI (10-15.75 Gy) and in 97% of females treated with total abdominal irradiation (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Gy) during childhood. 11,12 Using our knowledge and understanding of the radiosensitivity of human oocytes, it is now possible to predict the estimated sterilizing dose after any given dose of radiotherapy at any given age based on the application of the mathematical solution to our model for natural oocyte decline (Fig.…”
Section: Radiation and The Hypothalamic-pituitaryovarian Axismentioning
confidence: 99%
“…The somatic cells of the testis are more resistant than the germ cells, and Leydig cell dysfunction is not observed until doses of 20 Gy in prepubertal boys and 30 Gy in sexually mature males. 29 Within the pediatric and adolescent age groups, testicular damage occurs with direct irradiation of the testes (eg, in the management of leukemia). 30 In patients with leukemic infiltration of their testes, radiation doses of 24 Gy are used, and this results in permanent azoospermia.…”
Section: The Effect Of Radiotherapy On Testicular Functionmentioning
confidence: 99%
“…Entretanto, a falência compensada (níveis elevados de LH e normais de testosterona) não é infreqüente. Doses acima de 20 Gy são requeridas para o dano das células de Leydig, as quais parecem ser mais vulneráveis no testículo pré-púbere do que no adolescente (37). Irradiação gonadal pode causar dano das células germinativas em ambos os sexos, sendo o tecido testicular mais sensível que o ovariano.…”
Section: Distúrbios Gonadaisunclassified